Stand Improvement - SenGupta, J. N. (Indian Forester, 1937)
The three basic methods (viz., felling, girdling and poisoning) of eliminating undesirable trees have been compared in all essential details with a view to their practical application to experiments on natural regeneration in tropical evergreen forests.